2018
DOI: 10.1016/j.ejpb.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a crystalline salt of indomethacin and tromethamine by hot melt extrusion technology

Abstract: Although salt formation is the most ubiquitous and effective method of increasing the solubility and dissolution rates of acidic and basic drugs, it consumes large quantities of organic solvents and is a batch process. Herein, we show that the dissolution rate of indomethacin (a poorly water-soluble drug) can be increased by using hot melt extrusion of a 1:1 (mol/mol) indomethacin:tromethamine mixture to form a highly crystalline salt, the physicochemical properties of which are investigated in detail. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Whereas, if the pKa difference >3, then it can form a salt-type multicomponent crystal [31,32]. The pKas of MA and TM are reported as 4.2 and 8.07, respectively [11,33]. In the present study, the difference in pKa between these two solid phases is 3.87 (>3).…”
Section: Resultsmentioning
confidence: 42%
See 1 more Smart Citation
“…Whereas, if the pKa difference >3, then it can form a salt-type multicomponent crystal [31,32]. The pKas of MA and TM are reported as 4.2 and 8.07, respectively [11,33]. In the present study, the difference in pKa between these two solid phases is 3.87 (>3).…”
Section: Resultsmentioning
confidence: 42%
“…The lower the melting point of the solid phase, the weaker the lattice energy of the crystalline phase. Hence, the dissolution rate is faster [18,24,33,36]. Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR pattern revealed that breakdown of the intermolecular hydrogen bond of crystalline drug had taken place with the formation of hydrogen bond between the drug and the polymer. This could be confirmed by slight shift of IR bands related to hydroxyl group to lower side indicates the hydrogen bonding [5,9].…”
Section: Infrared Spectroscopic Studymentioning
confidence: 64%
“…It is a poorly water soluble antirheumatic agent. In literature attempts has been mase to improve the dissolution rate of indomethacin by various techniques like supersaturable delivery systems such as amorphous self-micellizing solid dispersions (SmSDs) [5] amorphous indomethacin coating with chitosan [6] mesoporous silica nanorods [7], spray drying with silica, polyvinylpyrrolidone (PVP) or 2-hydroxypropyl-β-cyclodextrin (HPβCD) [8] Indomethacin:tromethamine a highly crystalline salt by hot melt extrusion technology [9] melt-electrospun fibers (MSFs) [10], Solid dispersions by modified melt and quench-cooling (QC) method with graft copolymer (Soluplus®) or polyol sugar alcohol (xylitol) [11], microwave assisted in situ amorphization of indomethacin with PVP [12], coamorphous salts of indomethacin-lysine [13] .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Typically, amorphous solid dispersions result in a supersaturated solution of the poorly watersoluble drugs during the dissolution process both in vitro and in vivo, which enhances oral bioavailability. [18][19][20][21] To date, however, selection of an appropriate polymer for the preparation of an amorphous solid dispersion on the basis of structure-activity relationships remains challenging, and the optimal polymer-to-drug ratio continues to be determined using empirical data. [18][19][20][21] To date, however, selection of an appropriate polymer for the preparation of an amorphous solid dispersion on the basis of structure-activity relationships remains challenging, and the optimal polymer-to-drug ratio continues to be determined using empirical data.…”
mentioning
confidence: 99%